El aporte de la comunicación y las relaciones públicas en campañas de prevención contra la violencia hacia la mujer en universidades del Distrito Metropolitano de Quito, caso Universidad de las Américas y Pontificia Universidad Católica de Quito, promovido por ONU Mujeres - Razza Gaibor, Lizbeth Cristina (2015)
This work objective aims to prevent gender violence in universities located in the metropolitan district of Quito city by implementing a communication and public relations campaign, dedicated to both gender students attending to the “Universidad de Las Americas” and “Pontificia Universidad Católica”. The project is boosted by ONU Mujeres, an United Nations office dedicated to gender equality and women enforcement. The main transversal axis is education searching sensitize and built knowledge to the youngsters empowering social knowledge about gender violent practices. There are four chapters in the theoretical frame of this research. Chapter one: A study about understanding of communication campaigns. Chapter two: Genders violence and the work of ONU Mujeres in the United Nations office, Superior education law related to gender violence protection, and comparative analyses among the gender law in lay and catholic institutions, finally an study of both university education models. Chapter three: Research instruments and methodology to get information from objective target in order to establish their cause knowledge theme perception and communicational needs in such a way to create a communication approach for the two institutions. A multimodal qualitative and quantitative focusing in field research and the expert institutional sample was done to get and draw final conclusions related to violence, psychological, law enforcement and communication aspects. Chapter four is a FODA and cause effect analyses to build objectives strategy and tactics which are the basis of the preventive communicational campaign. Conclusions and recommendations related to this work are presented.